Implementación de dos bioensayos de remediación de suelo contaminados por hidrocarburos derivados del petróleo con la utilización de: impatiens balsamina & nephrolepis exaltata, en el cantón francisco de Orellana, provincia de Orellana - Ramírez Peral, Silvana Katterine (2016)
The purpose of this research was to carry out the implementation of two bioassays soil remediation contaminated with petroleum hydrocarbons location: Impatiens balsamina & Nephrolepis exaltata, in the Canton Francisco de Orellana, Orellana Province; the floor was characterized by performing physical-chemical laboratory analysis determined the degree of concentration of hydrocarbons in the soil of the 12 automotive workshops representative mechanical workshops Francisco de Orellana Canton obtaining the following values: Cadmium 13,75 mg/kg; Nickel 159.99 mg/kg; Lead 624.58 mg/kg; Total hydrocarbons 9897.57 mg/kg; aromatic hydrocarbons 9.54 mg/kg and pH 3.94, same values were compared with RAOHE Table six, in which the parameters and limits for the identification and remediation of contaminated soils in all phases of the industry set hydrocarbons, including service stations, of which they obtained values exceed these limits. a system of Phytoremediation in order to mitigate environmental impacts that has been occurring from improper use of petroleum hydrocarbons, the prototype that design was by two plots of ex situ bioassays using Impatiens balsamina & Nephrolepis exaltata was designed and a witness. the efficiency of plants as clearing agent is determined by a laboratory analysis bromatological and laboratory analysis of soil to determine if it is effective to use these plants in soil remediation. Statistically there is a significant degree between the parameters established between the two species, but empirically it can be said that Impatiens balsamina (L) Huth decontaminated and accumulates more than Nephrolepis exaltata (L) Schott.